Building Democracy In Latin America: United States Foreign Aid For Haiti - Arindrayani, Angelica (Global Strategis, 2024)
This article provides an overview, implications, and challenges that arise at the intersection of international political, economic, social, and environmental dilemmas that intervened in Haiti's efforts to build the stability of its democracy during the pre-Cold War period until recently. By providing United States Agency for International Development (USAID)'s trend of democratic assistance to the Latin American region and the presidential leadership model that may explain Haiti's failure to combat political instability, this article has positioned the Haitian government as a contributor to Haiti's permanent crisis, with the role of an elite society taking control of the interim government system and the civil society as the party to bear the consequences. The occurrence of a devastating earthquake has tested Haiti and resulted in more and more Haitians migrating to the United States. This condition exacerbated Haiti's status as a "failed state" and the need for sustained commitment and long-term international stabilization efforts. By applying the analytical explanatory method, the results show that if Haiti is to escape its permanent political instability, a more comprehensive policy-making paradigm shift is needed beyond just democratic assistance from USAID. Keywords: Democratic Aid, Haiti, USAID, Democracy, Foreign Aid. Artikel ini mengulas ikhtisar, implikasi, dan tantangan yang muncul di persimpangan dilema politik, ekonomi, sosial, dan lingkungan internasional yang mengintervensi Haiti dalam upaya membangun stabilitas demokrasinya selama periode sebelum Perang Dingin hingga baru-baru ini. Dengan menyediakan tren bantuan demokratis Badan Pembangunan Internasional Amerika Serikat (USAID) ke wilayah Amerika Latin dan model kepemimpinan presiden yang mungkin bisa menjadi alasan atas tidak berhasilnya Haiti melawan ketidakstabilan politik, artikel ini telah menempatkan pemerintah Haiti sebagai kontributor krisis permanen Haiti, dengan peran masyarakat elit yang mengambil alih kontrol sistem pemerintahan sementara masyarakat sipil menjadi pihak menanggung akibatnya. Adapun terjadinya gempa bumi dahsyat telah menguji Haiti dan mengakibatkan semakin banyak penduduk Haiti yang bermigrasi ke Amerika Serikat. Kondisi ini kemudian memperburuk status Haiti sebagai sebuah "negara gagal" dan perlunya komitmen berkelanjutan serta upaya stabilisasi internasional berjangka panjang. Dengan menerapkan metode eksplanatif secara analitis, hasil menunjukkan bahwa jika Haiti ingin melepaskan diri dari ketidakstabilan politik permanennya, diperlukan pergeseran paradigma pembuat kebijakan yang lebih komprehensif daripada hanya sekedar bantuan demokratis dari USAID. Kata-kata kunci: Bantuan Demokratis, Haiti, USAID, Demokrasi, Bantuan Luar Negeri.